Integrasi Karakter Peduli Lingkungan Dalam Program Sekolah Adiwiyata di SDN Cipondoh 5 - Dewi Fortuna; Muhammad Fauzan Muttaqin; Pebrisa Amrina (Jurnal Elementaria Edukasia, 2023)
This research aims to find out how the character of caring for the environment can be integrated into the Adiwiyata school program at SDN Cipondoh 5. This research uses a descriptive qualitative method, a case study type. Data collection uses observation; interviews with informant sources, the school principal, 2 teachers, 2 people in charge of the Adiwiyata program, and 5 students; and documentation studies. The data validity techniques used by researchers are technical triangulation and source triangulation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Based on the research results, it shows that the Adiwiyata school program can grow and improve the environmentally caring character of students at SDN Cipondoh 5 as they get used to it at school. Integration is carried out through the curriculum, development of environment-based learning tools, activities to bring your own food and drinking bottles, training to make biopore holes, clean Friday activities. The integration carried out by the school also collaborates with the school community, student parents, health centers and other related agencies. The obstacles faced are related to the lack of coordination between teachers and inadequate land in optimizing the adiwiata program. The implications are for schools in overcoming obstacles through integrating the Adiwiyata program in collaboration with environmental agencies so that they can regain the national level Adiwiyata school certificate award